The influence of longitudinal reinforcement on shear capacity of reinforced concrete members without shear reinforcement - Marta Słowik (Budownictwo i Architektura, 2014)
In the paper, the influence of longitudinal reinforcement on shear capacity of reinforced concrete members without shear reinforcement is discussed. The problem is analyzed on the basis of the author’s own test results and tests results reported in the professional literature. It has been concluded that longitudinal reinforcement has an effect on shear capacity especially in members of shear span-to-depth ratio a/d < 2,5. The test results have also been used to verify standard methods of calculating the shear capacity in reinforced concrete members without shear reinforcement given in Eurocode 2, ACI Standard 318 and Model Code 2010.